2014
DOI: 10.1007/s12264-013-1410-3
|View full text |Cite
|
Sign up to set email alerts
|

Lipid metabolism in Alzheimer’s disease

Abstract: Lipids play crucial roles in cell signaling and various physiological processes, especially in the brain. Impaired lipid metabolism in the brain has been implicated in neurodegenerative diseases, such as Alzheimer's disease (AD), and other central nervous system insults. The brain contains thousands of lipid species, but the complex lipid compositional diversity and the function of each of lipid species are currently poorly understood. This review integrates current knowledge about major lipid changes with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(62 citation statements)
references
References 174 publications
0
62
0
Order By: Relevance
“…We also observed that in the absence of overt dementia pathology, both circulating and brainderived EVs from hypoperfused mice contain proteins already implicated in neuronal atrophy, neuroinflammation, neurotoxicity and maintenance of brain tissue integrity, including hippocalcin, neurofascin, NCAM1 and MOG. These findings indicate that hypoperfused mice exhibit key features of AD, including BBB hyperpermeability (33,54,71), BBB-associated neuroinflammation (16,37,73), associated amyloid-β and tau neurotoxicity (3,51) and impaired lipid metabolism (52). Our findings further indicate that brain EVs incorporate both mediators of neuroprotection and hallmarks of neuronal damage, consistent with the concept that these vesicles act as a "doubled-edged sword" in AD (6), and shed important new light on specific protein mediators that might contribute to this functional dichotomy.…”
Section: Discussionmentioning
confidence: 85%
“…We also observed that in the absence of overt dementia pathology, both circulating and brainderived EVs from hypoperfused mice contain proteins already implicated in neuronal atrophy, neuroinflammation, neurotoxicity and maintenance of brain tissue integrity, including hippocalcin, neurofascin, NCAM1 and MOG. These findings indicate that hypoperfused mice exhibit key features of AD, including BBB hyperpermeability (33,54,71), BBB-associated neuroinflammation (16,37,73), associated amyloid-β and tau neurotoxicity (3,51) and impaired lipid metabolism (52). Our findings further indicate that brain EVs incorporate both mediators of neuroprotection and hallmarks of neuronal damage, consistent with the concept that these vesicles act as a "doubled-edged sword" in AD (6), and shed important new light on specific protein mediators that might contribute to this functional dichotomy.…”
Section: Discussionmentioning
confidence: 85%
“…Brain proteomic analysis in humanized APOE4 knock-in mice revealed down-regulation of enzymes involved in metabolic processes from glycolysis, TCA cycle, amino acid metabolism, and to lipid metabolism [47]. Metabolomic analysis in AD patients also confirmed alternations in brain lipid profiles [51][52][53]. Mechanistic and clinical research revealed that brain lipid metabolic dysregulation is associated with white matter disintegration [54,55], and can drive inflammatory responses in the brain to modulate the risk of LOAD [52,[56][57][58].…”
Section: Introductionmentioning
confidence: 99%
“…Extensive nutritional studies have established a role for diet in moderating the pathogenesis, symptoms, and progression of AD [2,3]. Cholesterol was among the first of these associations, implicated when mutations in the apoE lipoprotein transporter emerged as a major genetic predisposition for AD [4].…”
Section: Everyday Life Variablesmentioning
confidence: 99%
“…Cholesterol was among the first of these associations, implicated when mutations in the apoE lipoprotein transporter emerged as a major genetic predisposition for AD [4]. Subsequent studies revealed that cholesterol may directly modulate β‐amyloid (Aβ) oligomerization [5] and may further drive the pathogenic misfolding of Aβ responsible for its aggregation into plaques [3,6]. Saturated and trans fats are similarly associated with deleterious risk and more rapid disease progression.…”
Section: Everyday Life Variablesmentioning
confidence: 99%